2020
DOI: 10.1152/ajplung.00084.2019
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 channel mediates adventitial fibroblast activation and adventitial remodeling in pulmonary hypertension

Abstract: Pulmonary arterial adventitial fibroblasts (PAF), the most abundant cellular constituent of adventitia, act as a key regulator of pulmonary vascular wall structure and function from the outside-in. Previous studies indicate that transient receptor potential vanilloid 4 (TRPV4) channel plays an important role in the development of pulmonary hypertension (PH), but no attention has been given so far to its role in adventitial remodeling. In this study, we thus investigated TRPV4 implication in PAF activation occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…TRPC mediated the synthesis of extracellular matrix proteins by up-regulating the expression of type I collagen and fibronectin, thus participating in pulmonary adventitia remodelling. 54 TRPC has a direct or indirect effect on the regulation of calcium ions. GPCRs and various angiogenic substances (5-HT, Ang II, ET-1, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…TRPC mediated the synthesis of extracellular matrix proteins by up-regulating the expression of type I collagen and fibronectin, thus participating in pulmonary adventitia remodelling. 54 TRPC has a direct or indirect effect on the regulation of calcium ions. GPCRs and various angiogenic substances (5-HT, Ang II, ET-1, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an increased Ca 2+ entry through TRPV4 contributed to an enhanced PASMCs contraction, migration and proliferation triggered by chronic hypoxia [118]. More recently, TRPV4 was studied in pulmonary arterial adventitial fibroblasts using TRPV4-KO mice, siRNA and the pharmacologic inhibition of TRPV4 [93]. This study revealed that TRPV4 played an important role in the proliferation, migration and synthesis of the extracellular matrix, hallmarks of the pathogenesis of PAH [93].…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 93%
“…TRPV1 and TRPV4 activation evokes Ca 2+ influx, proliferation and contraction of PASMCs [85,89,90,92]. TRPV4 plays a role in fibroblast proliferation and the synthesis of the extracellular matrix in lungs [93].…”
Section: Pulmonary Arterial Hypertension Trpc Trpvmentioning
confidence: 99%
See 2 more Smart Citations